A basic analysis of electrochemical impedance in Bismuth Ferrite based solar cell. (2021) - Vignesh, G.; MuthuKumar, A.; Janet Sherly, I.; John Peter, I.; Ramachandran, K.; Nithiananthi, P.
Abstract: Power conversion efficiency of Dye-Sensitized Solar Cells (DSSCs) depend not only on the dye to sensitize and the bandgap of photoanode but also on the cumulative effect of electrochemical properties of the electrolyte, dye and ion transport layers. This is a simple theoretical model for the impedance analysis of DSSC. This is a modified theoretical simulation with resistive weight-factor on electrochemical impedance of DSSC made of Bismuth Ferrite (BFO) and Aluminum-Copper doped Zinc Oxide-BFO (BiFeO3-(Al, Cu) ZnO) nanocomposite. Electron transport lifetime and charge collection efficiency are computed. The present work gives a fairly good explanation of the experimental measurements.